Therapeutic ultrasound related pain threshold in elite track & field athletes with tibial bone stress injuries - Malliaropoulos, N.; Bikos, G.; Tsifountoudis, I.; Alaseirlis, D.; Christodoulou, D.; Padhiar, N.; Maffulli, N. (The Surgeon, 2023)
Objective: Tibial stress injuries are challenging in terms of early diagnosis, management strategy, and safe return-to-play. In the present study, pain production associated with the application of therapeutic ultrasound (TUS) was used as a primary diagnostic tool to assess tibial bone stress injuries, and the sensitivity of this procedure was compared with Magnetic Resonance Imaging (MRI). Subject and methods: The study was designed as a retrospective analysis of prospectively collected data on tibial bone stress injuries in elite Track and field athletes attending the National Track and Field Athletics Centre in Thessaloniki, Greece, in the period 1995-2007. All patients underwent evaluation by TUS, and the sensitivity of the procedure was compared with MRI. Results: Four of 29 athletes showed a positive TUS examination for stress injury while MRI showed normal findings. Additionally, 5 athletes evidenced MRI findings typical of a tibial bone stress injury, while TUS evaluation was negative. Using MRI as the standard, TUS displayed a sensitivity of 79.2%. Conclusion: Therapeutic ultrasound is a reproducible modality with satisfactory reliability and sensitivity related to MRI, and could represent a useful tool for clinicians to primarily assess suspected tibial bone stress injuries in high qualification Track and Field athletes.